2017
DOI: 10.1016/j.cpa.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Globalisation, accounting and developing countries

Abstract: Accounting is an instrument and an object in globalisation but its impact and manifestation is not uniform across Northern developed countries and Southern developing countries (DCs). This paper reviews contributions on globalisation and its influence on accounting in DCs, and identifies important research gaps. It examines the role of accounting in changing development policies, from state capitalism through neo-liberal market-based to good-governance policies. It then considers specific accounting issues, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
357
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(397 citation statements)
references
References 209 publications
8
357
0
9
Order By: Relevance
“…Institutional pressures for the adoption of IPSASs and their implementation have drawn more critics in Africa as compared with other developing contexts (Hopper et al, 2017). Wynne (2013) states that more than 30 governments in Africa have attempted to adopt the Cash Basis of IPSAS in the last decade to cope with external pressures, but the standard's requirements have proved to be impractical in their specific contexts.…”
Section: Ipsass In Africamentioning
confidence: 99%
See 2 more Smart Citations
“…Institutional pressures for the adoption of IPSASs and their implementation have drawn more critics in Africa as compared with other developing contexts (Hopper et al, 2017). Wynne (2013) states that more than 30 governments in Africa have attempted to adopt the Cash Basis of IPSAS in the last decade to cope with external pressures, but the standard's requirements have proved to be impractical in their specific contexts.…”
Section: Ipsass In Africamentioning
confidence: 99%
“…Although not to the same extent as studies of Western countries, research covering the efforts of developing countries to streamline their public sector accounting systems has increased in recent years (Adhikari and Mellemvik, 2010;Hopper et al, 2017). Particularly, international organisationsthe World Bank (WB) and the International Monetary Fund (IMF) -push ACC.A and IPSASs as being allegedly important to improve day-to-day accounting (Goddard et al, 2016;Harun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining 49 countries, Cieslewicz () found that IFRS is often modified to reflect underlying institutional distinctiveness of a nation. Accounting researchers have further focused on how this issue has played out in countries with developing economies (often called emerging markets), where high demand for foreign direct investment and aid from the World Bank have encouraged IFRS adoption (see Mir and Rahaman, ; Tyrrall et al ., ; Ezzamel and Xiao, ; Karampinis and Hevas, ; Albu and Albu, ; Andrews, ; Hopper et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Development policies in Africa have veered from state socialism to neo‐liberalism, and currently around good governance (Hopper et al., ). A recurring finding is that (regardless of approach), when sound accounting and accountability systems are adopted, they often play a ceremonial role to gain legitimacy from citizens and external funders rather than aiding ministerial and parliamentary scrutiny, operational decision‐making, and accountability (Hopper, Tsamenyi, Uddin, & Wickramasinghe, ).…”
Section: Accounting Reform In Africa: Reconciling Participatory Develmentioning
confidence: 99%